Pengaruh Umpan Balik dan Minat Belajar terhadap Hasil Belajar Bulutangkis: Studi Eksperimen pada Siswa Kelas VIII SMP Negeri 165 Jakarta - Putu Rusmiati (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2016)
The aim of this research is to find out the influence of feedback and interest in learning toward the result of badminton learning. The sample of this research concept of 40 student grade VIII Junior High School of 165 Jakarta and done in experimental study 2 x 2 by level design. The data were analyzed by using analyzed of varians (ANAVA) and then continued with Tuckey Test were used to test the hypotheses at the level of significance ? = 0,05. The results of the research show that (1) in general, there is a significance difference between delayed feedback and direct feedback toward the result of badminton learning (Fo 4,19 > 4,11 Ft) and delayed feedback is better than direct feedback for the result of badminton learning, (2) there is an interaction between feedback and interest in learning for the result of badminton learning (Fo 23,96 > 4,11 Ft), (3) for high interest in learning, delayed feedback is better than direct feedback for the result of badminton learning (Qo 13,5 > 4,33 Qt), and (4) for low interest in learning, direct feedback is better than delayed feedback for the result of badminton learning (Qo 5,68 > 4,33 Qt).